A method for testing the film adhesion of a glass
By repeatedly rubbing the surface of photovoltaic glass to simulate wind and sand abrasion, the cumulative number of abrasion cycles of the film layer is quantified, solving the problem of difficulty in distinguishing the abrasion resistance of photovoltaic glass film layers in existing technologies, and realizing accurate film layer adhesion testing and evaluation.
Patent Information
- Application Number
- CN202611207535.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-11-03
Smart Images

Figure CN123028918A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic glass technology, and in particular to a method for testing the adhesion of glass film. Background Technology
[0002] Photovoltaic glass is the core encapsulation material of photovoltaic modules. Through tempering and surface coating treatment, it integrates functions such as anti-reflection, wear resistance, stain resistance, and weather resistance, directly determining the module's light transmission efficiency, mechanical protection capabilities, and long-term outdoor reliability. With the iteration of high-efficiency battery technology, photovoltaic glass continues to upgrade towards ultra-thinness, high light transmission, and multi-functional composites. The stability of its surface functional films has become a key factor restricting module lifespan and power generation revenue.
[0003] Currently, the industry generally uses pencil hardness to evaluate the ability of a coating to resist mechanical damage. This method only reflects the coating's resistance to one-time scratches and is seriously inconsistent with the cumulative fatigue wear failure mechanism caused by repeated impacts from sand particles in outdoor high-wind and sandy environments. As high-performance wear-resistant glass continues to evolve, the pencil hardness of products is mostly concentrated in the high range of similar hardness, making it difficult to effectively distinguish performance differences. At the same time, there is a lack of standardized quantitative testing methods and judgment rules for the cumulative wear effect of glass coatings both domestically and internationally. This makes it difficult to accurately, stably, and reproducibly quantify the strength of glass coatings, and thus cannot provide reliable support for material research and development, quality control, and product selection. Summary of the Invention
[0004] This application discloses a method for testing the strength of a glass film, which can distinguish the strength values (i.e., abrasion resistance) of different photovoltaic glasses with similar hardness.
[0005] To achieve the above objectives, some embodiments of this application provide a garment processing apparatus, including: A friction element is used to rub the same area of the surface film layer of the glass sample to be tested for a preset number of times, wherein the hardness of the friction element is less than the minimum hardness of the surface film layer. Observe whether the film layer peels off in the friction area, wherein the film layer peeling off is defined as visible peeling or flaking of the surface film layer; If no film peeling is observed in the friction area, repeat the above two steps until film peeling is observed in the friction area for the first time. One round of friction of the preset number of times is recorded as one test cycle. After removing the number of frictions in the test cycle in which the film peels off, the total number of frictions in the remaining test cycles is calculated, and the total number of frictions is recorded as the strength value of the glass sample to be tested.
[0006] As an optional implementation, the surface film layer has a starting point and a round trip point. The friction element moves from the starting point to the round trip point and then from the round trip point back to the starting point, which is recorded as one friction cycle.
[0007] As an optional implementation, the movement of the friction element between the starting point and the reciprocating point is a linear reciprocating motion, wherein the distance between the starting point and the reciprocating point is 45mm~55mm.
[0008] As an optional implementation, rubbing the same area of the surface film of the glass sample to be tested with a friction element for a preset number of cycles includes: A test trolley capable of reciprocating along the horizontal direction is used to drive the friction component to rub the same area of the surface film of the glass sample under test for a preset number of times. The test trolley has a counterweight that can apply a preset downward vertical pressure to the friction component.
[0009] As an optional implementation, the friction element moves at a speed of 8 mm / s to 12 mm / s between the starting point and the reciprocating point.
[0010] As an optional implementation, the friction element is a rod-shaped structure, and the angle between the friction element and the surface film layer of the glass sample to be tested is 43°~47°; and / or, The friction element is made of natural rubber or neoprene rubber, and its Shore A hardness is 65~75.
[0011] As an optional implementation, between the steps of rubbing the same area of the surface film of the glass sample to be tested with a friction element for a preset number of times and observing whether the film peels off in the rubbed area, the glass film adhesion test method further includes: Clean the area of the surface film layer of the glass sample to be tested that has been rubbed.
[0012] As an optional implementation, the step of observing whether film peeling occurs in the friction area includes: The friction area was observed using an optical microscope to determine if film peeling or flaking occurred. Specifically, if the area of peeling or flaking of the surface film was greater than 0.1 mm, it was considered a positive result. The occurrence of film peeling is determined when the peeling or flaking area of the surface film is less than or equal to 0.1 mm. It is determined that no film layer has peeled off.
[0013] As an optional implementation, if no film peeling is observed in the friction area after the glass sample under test has completed a preset number of rubbing cycles, the test is stopped, and the strength value of the glass sample under test is greater than the preset number of rubbing cycles.
[0014] As an optional implementation, after recording the strength value of the glass sample to be tested, the glass film strength test method further includes: Take multiple identical glass samples to be tested and test their fastness values respectively; The median of the fastness values of all the same type of glass samples to be tested is taken as the fastness value of this type of glass sample.
[0015] Compared with the prior art, the beneficial effects of this application are at least as follows: This application provides a method for testing the adhesion of a glass film. It uses a friction component with a hardness less than that of glass to repeatedly rub the same area, simulating the real failure mechanism of long-term abrasive wear from outdoor wind and sand using a cumulative wear method. This ensures the test results closely match the actual service behavior of the film, more accurately reflecting its resistance to fatigue and detachment. Furthermore, by using the total number of friction cycles before the first film detachment occurs as the adhesion value, the quantitative number of friction cycles achieves precise characterization of the film's adhesion. This effectively distinguishes glass products with highly similar pencil hardness, providing a quantifiable and comparable evaluation basis for material selection, process optimization, and quality control, thus enhancing the test's discriminative power and application value. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a flowchart of the glass film adhesion testing method disclosed in the embodiments of this application; Figure 2 This is a schematic diagram of the structure of the test cart and friction component disclosed in the embodiments of this application; Figure 3 The results of the strength tests for conventional glass and abrasion-resistant glass disclosed in the embodiments of this application are as follows; Figure 4 This is a schematic diagram of conventional glass before the film layer peels off, as disclosed in the embodiments of this application. Figure 5 This is a schematic diagram of conventional glass after the film layer has peeled off, as disclosed in the embodiments of this application; Figure 6 This is a schematic diagram of the wear-resistant glass before the film layer peels off, as disclosed in the embodiments of this application. Figure 7 This is a schematic diagram of the wear-resistant glass after the film layer has peeled off, as disclosed in the embodiments of this application; Figure 8This is a comparison chart showing the results of pencil hardness testing on conventional glass and wear-resistant glass disclosed in the embodiments of this application, and the test method of this application.
[0018] Explanation of reference numerals in the attached figures: 1- Glass sample to be tested; 2- Friction component; 3- Test carriage; α- Angle between the friction component and the surface film of the glass sample to be tested. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0020] The directional or positional terms used in this application, such as "upper," "lower," "inner," and "outer," are based on the directions shown in the accompanying drawings and are used only for descriptive purposes, not to limit the actual location or structure. Some terms may have other meanings in different contexts, and those skilled in the art should understand them according to the specific context.
[0021] The terms "installation," "setup," and "connection," etc., should be interpreted broadly to include, but are not limited to, fixed or detachable, mechanical or electrical, direct or indirect connection methods. The terms "first," "second," etc., are used only to distinguish objects and do not indicate importance or order. Unless otherwise stated, "multiple" refers to two or more.
[0022] The field of home appliance technology encompasses a wide range of product categories, including but not limited to refrigerators, washing machines, air conditioners, microwave ovens, dishwashers, and vacuum cleaners. The technological development trends for these products primarily focus on intelligentization, energy conservation and environmental protection, optimized user experience, and the application of new materials. Optimized user experience is achieved through design innovation and functional enhancement to meet consumers' demands for health, convenience, and personalization.
[0023] Photovoltaic glass is the core encapsulation material of photovoltaic modules. Through tempering and surface coating treatment, it integrates functions such as anti-reflection, wear resistance, stain resistance, and weather resistance, directly determining the module's light transmission efficiency, mechanical protection capabilities, and long-term outdoor reliability. With the iteration of high-efficiency battery technology, photovoltaic glass continues to upgrade towards ultra-thinness, high light transmission, and multi-functional composites. The stability of its surface functional films has become a key factor restricting module lifespan and power generation revenue.
[0024] Currently, the industry commonly uses pencil hardness testing to evaluate the ability of glass coatings to resist mechanical action. This test method involves using pencils of different hardnesses (1H~9H) to scratch the glass surface and observing whether permanent scratches appear. The highest pencil hardness that does not produce a scratch is the test result.
[0025] Pencil hardness testing reflects the ability of a film layer to resist a single scratch from a sharp object. However, in actual service, especially in windy and sandy environments, the glass surface is mainly subjected to repeated impacts from sand particles and abrasive wear, leading to progressive fatigue and detachment of the film layer. The failure mechanisms of the two are different, and pencil hardness testing cannot effectively predict the wear resistance life of the film layer in actual use.
[0026] The differentiation of high-performance wear-resistant glass is insufficient. With the continuous upgrading of glass coating technology, the pencil hardness test results of photovoltaic glass are often concentrated in the high hardness range of 7H to 9H, making it difficult to effectively distinguish the differences in wear resistance performance of different products and failing to provide effective guidance for product development and selection.
[0027] Currently, there is a lack of standardized testing methods to simulate the cumulative wear effect.
[0028] Therefore, there is an urgent need to develop a glass film adhesion test method that can simulate the cumulative wear effect of the film layer, effectively distinguish different wear-resistant glass products, and is easy to operate.
[0029] Based on this, this application discloses a glass film strength test method that can distinguish the strength values (i.e., abrasion resistance) of different photovoltaic glasses with similar hardness.
[0030] The present technical solution will be further described below with reference to the embodiments and accompanying drawings.
[0031] Photovoltaic glass is the outermost protective and light-transmitting core material of photovoltaic modules. The main structure is based on ultra-white rolled or float low-iron glass sheets, which are physically tempered to form high-strength safety glass. It is the mechanical load-bearing and basic protective part of the entire structure.
[0032] To improve power generation efficiency and service life, one or more functional films are prepared on its surface, commonly including anti-reflective films, wear-resistant films, anti-fouling films, and weather-resistant films. These films are directly attached to the surface of tempered glass and together determine the light transmittance, wear resistance, and long-term reliability of the glass.
[0033] Overall, the typical structure of photovoltaic glass consists of a tempered low-iron glass substrate and a single-sided or double-sided functional film layer. This ensures high light transmittance and high mechanical strength, while also achieving key properties such as anti-reflection, wear resistance, and anti-aging. It is an important guarantee for the long-term stable operation of photovoltaic modules outdoors.
[0034] Please see Figure 1 , Figure 1This is a flowchart of a glass film adhesion testing method disclosed in an embodiment of this application. The embodiment of this application discloses a glass film adhesion testing method, which includes: Step S1: Use the friction element 2 to rub the same area of the surface film of the glass sample 1 to be tested for a preset number of times. The hardness of the surface film of photovoltaic glass usually has a range value, wherein the hardness of the friction element 2 is less than the minimum hardness of the surface film of photovoltaic glass. Step S2: Observe whether the film layer peels off in the friction area. Film layer peeling is defined as visible peeling or flaking of the film layer. Step S3: If no film peeling is observed in the friction area, repeat the above two steps until film peeling is observed in the friction area for the first time. Step S4: One preset number of rubbing cycles is recorded as one test cycle. After removing the number of rubbing cycles in which the film peels off, the total number of rubbing cycles in the remaining test cycles is calculated, and the total number of rubbing cycles is recorded as the strength value of the glass sample 1 to be tested.
[0035] The strength value of the glass film can be understood as the wear resistance of the glass film, which is reflected in the wear resistance, abrasion resistance, resistance to repeated friction, adhesion to glass, peel strength, etc. of the surface film. The higher the strength value, the greater the hardness of the surface film of the glass sample, and vice versa.
[0036] For example, taking a preset number of times as 10, if the film layer is found to peel off in the rubbing area after the rubbing member 2 rubs the same area of the glass sample 1 to be tested 10 times, the fastness value of the glass sample 1 to be tested is determined to be 0; if the film layer is not found to peel off in the rubbing area, the rubbing member 2 is used to continue rubbing the same area of the glass sample 1 to be tested, and the results are observed every 10 times. For example, after 40 rubbings, if the film layer is found to peel off in the rubbing area, the fastness value of the glass sample 1 to be tested is 30.
[0037] In this way, by using a friction component 2 with a hardness less than that of glass to repeatedly rub the same area, the cumulative wear simulates the real failure mechanism of long-term abrasive wear of outdoor wind and sand, rather than the one-time sharp scratch of the traditional pencil hardness test. This makes the test results highly consistent with the actual service behavior of the film layer, and can more realistically reflect the fatigue resistance and peeling ability of the film layer, thus solving the problem of the disconnect between the existing test and the actual working conditions.
[0038] Meanwhile, by using the total number of rubs before the first film peeling as the adhesion value, the adhesion of the film can be accurately characterized by quantifying the number of rubs. This can effectively distinguish glass products with similar pencil hardness, providing a quantifiable and comparable evaluation basis for material selection, process optimization and quality control, and significantly improving the test's distinguishability and application value.
[0039] It is understandable that the material of friction component 2 can be nitrile rubber (NBR), which is wear-resistant, oil-resistant, does not shed shavings, has stable rebound, and has consistent long-term reciprocating friction performance, making it the best alternative material; it can also be polyurethane rubber (PU / TPU), which has extremely strong wear resistance, tear resistance, small deformation, stable friction, long service life, and is suitable for long-cycle testing, etc. Therefore, the material of friction component 2 is not limited here.
[0040] In some embodiments, the surface film layer has a starting point and a round trip point. The friction element 2 moves from the starting point to the round trip point and then moves from the round trip point back to the starting point, which is recorded as one friction cycle.
[0041] Each friction cycle starts from the starting point and returns to the starting point at the return point. The stroke, path, and duration of each friction cycle are kept consistent to avoid inconsistent wear caused by half-stroke, single-stroke, or irregular movements. This ensures that the cumulative wear on the film layer is uniform and controllable, making the test results closer to the actual fatigue failure process.
[0042] Meanwhile, the reciprocating counting rule makes the fastness value statistics more accurate, can be performed according to the same standard, greatly reduces human error, and provides a reliable basis for subsequent periodic judgment and fastness calculation.
[0043] The movement path of the friction element 2 between the starting point and the return point can be a straight line or a curve, as long as the path from the starting point to the return point is the same as the path from the return point to the starting point. The above embodiment does not limit this.
[0044] In some embodiments, the movement of the friction member 2 between the starting point and the reciprocating point is a linear reciprocating motion, wherein the distance between the starting point and the reciprocating point is 45mm~55mm.
[0045] Limiting the motion of friction component 2 to linear reciprocating motion ensures a fixed friction trajectory and uniform and stable wear action, avoiding uneven local stress and wear superposition deviation caused by curved or irregular motion. This ensures that the frictional stress borne by the film layer is consistent and the cumulative wear effect is repeatable, making the film layer adhesion test more accurate.
[0046] If the distance between the starting point and the round trip point is less than 45mm, the friction stroke is too short, which will cause the film layer to be subjected to too many friction times in a local area. This can easily lead to excessive wear and premature failure in a local area, and cannot truly reflect the overall wear resistance of the film layer. At the same time, too short a stroke will also reduce the test discrimination, making it difficult to effectively identify the differences in fastness between different samples.
[0047] If the distance between the two is greater than 55mm, the friction stroke will be too long, which will increase the range and time of a single friction. This will easily lead to problems such as force deviation of friction component 2 and decreased motion stability. This will not only prolong the test cycle and reduce the test efficiency, but may also cause the wear uniformity to deteriorate due to the excessive stroke, affecting the accuracy and repeatability of the test results.
[0048] By controlling the spacing within the range of 45mm to 55mm, it is possible to ensure that the friction area is of a moderate size and that the film wear is uniform and sufficient, thus realistically simulating the actual working conditions of outdoor wind and sand abrasive wear. At the same time, it can maintain the stability of the movement of the friction component 2 and the efficiency of the test rhythm, making the fastness values clearly distinguishable and the results reproducible, which is suitable for the standardized and quantitative testing of the fastness of photovoltaic glass film.
[0049] The distance between the starting point and the round-trip point can be 45mm~48mm, 48mm~52mm, 50mm~55mm, etc. For example, it can be 45mm, 50mm, or 55mm.
[0050] In some embodiments, rubbing the same area of the surface film layer of the glass sample 1 to be tested with the friction element 2 for a preset number of cycles includes: using a test carriage 3 capable of reciprocating in the horizontal direction to drive the friction element 2 to rub the same area of the surface film layer of the glass sample 1 to be tested for a preset number of cycles. The test carriage 3 has a counterweight capable of applying a preset downward vertical pressure to the friction element 2.
[0051] In this way, by using a test trolley 3 that can move horizontally back and forth to drive the friction component 2, it is possible to ensure that the frictional motion is uniform, directional, and has a fixed trajectory, avoiding problems such as uneven force, unstable speed, and path deviation caused by manual operation. This allows the wear effect on the membrane layer to be controlled throughout the process, significantly improving the accuracy of the test results and the reproducibility of the operation.
[0052] The test trolley 3 is equipped with a counterweight that can apply a preset vertical downward pressure, which can stably control the normal pressure of the friction component 2 on the glass film layer, ensuring that the contact stress and wear intensity are consistent for each friction. This solves the defect of inconsistent wear degree caused by large fluctuations in manual pressure application, making the fastness test results more objective and comparable.
[0053] Overall, this technical solution directly reuses the commonly used test vehicle structure in the industry, which is simple to modify, low in cost, and easy to promote. While ensuring testing accuracy, it significantly reduces the development cost of special equipment.
[0054] The counterweight can be the sum of the test vehicle 3 and the added counterweight.
[0055] Optionally, the counterweight is 730g~770g.
[0056] If the counterweight is less than 730g, the normal pressure of friction component 2 on the film layer will be insufficient, which will lead to weak friction and low cumulative wear efficiency. The film layer will be difficult to achieve real fatigue detachment within a reasonable period, which will not only prolong the test time, but also cause the fastness value to be falsely high, making it impossible to distinguish the performance differences of different products, and losing the test's ability to differentiate and evaluate.
[0057] If the counterweight is greater than 770g, the pressure of friction component 2 on the film layer will be too high, which will cause the film layer to be excessively worn in a short period of time, and the film layer will easily fall off prematurely, resulting in a low fastness value. The test results cannot reflect the actual service performance.
[0058] By controlling the counterweight within the range of 730g to 770g, a stable and moderate positive pressure can be provided, allowing the friction component 2 to form an appropriate and continuous cumulative wear effect on the film layer. This can quickly induce the actual fatigue detachment behavior of the film layer and shorten the test cycle, while ensuring that the wear intensity is highly matched with outdoor working conditions. This results in clear distinction of fastness values and stable and reproducible test results, providing reliable test conditions for the accurate quantification of the fastness of photovoltaic glass film layers.
[0059] The counterweight can be 730mm~750mm, 750mm~760mm, 755mm~770mm, etc. For example, it can be 730mm, 750mm, or 770mm.
[0060] In some embodiments, the friction element 2 moves at a speed of 8 mm / s to 12 mm / s between the starting point and the reciprocating point.
[0061] If the speed of friction component 2 is less than 8 mm / s, the number of friction cycles the film layer experiences per unit time will be too few, and the cumulative wear rate will be too slow. This will not only lengthen the test cycle and reduce the detection efficiency, but also make it difficult for the film layer to actually fatigue and fall off within a reasonable cycle due to insufficient wear strength. This will result in an inflated fastness value and make it impossible to effectively distinguish the differences in wear resistance performance between different samples.
[0062] If the speed of friction component 2 is greater than 12 mm / s, the contact between friction component 2 and the film layer will be unstable and the local impact will be too large due to the excessive speed of movement. This will easily cause non-fatigue instantaneous damage to the film layer. At the same time, high-speed movement will also cause equipment vibration and trajectory deviation, reducing the accuracy and repeatability of test results.
[0063] By controlling the friction speed within the range of 8mm / s to 12mm / s, it is possible to ensure that the film layer is subjected to stable and uniform cumulative wear, while also ensuring that the test rhythm is moderate and efficient. At the same time, it is possible to ensure that the friction component 2 runs smoothly without impact, so that the fastness test data is accurate and highly distinguishable, and is suitable for standardized and quantitative testing of the fastness of photovoltaic glass film layers.
[0064] The speed of the friction element 2 between the starting point and the reciprocating point can be 8mm / s~10mm / s, 10mm / s~11mm / s, 11mm / s~12mm / s, etc. For example, it can be 8mm / s, 10mm / s, or 12mm / s.
[0065] In some embodiments, combined with Figure 2 , Figure 2 This is a schematic diagram of the test cart 3 and friction element 2 disclosed in the embodiments of this application. The friction element 2 is a rod-shaped structure, and the angle α between the friction element 2 and the surface film layer of the glass sample 1 to be tested is 43°~47°.
[0066] If the angle between the friction element 2 and the film layer on the surface of the glass to be tested is less than 43°, the vertical component of the friction element 2 on the film layer will be too small and the horizontal component will be too large, which will easily cause the film layer to be scratched and damaged, and will not be able to stably simulate the real abrasive fatigue wear. At the same time, if the angle is too small, the friction element 2 will also slide unstably and easily deviate, which will destroy the consistency of the test trajectory, resulting in large deviation and poor repeatability of the firmness results.
[0067] If the included angle is greater than 47°, the vertical pressure is too concentrated, and the local compressive stress of the friction component 2 on the film layer is too high, which will cause the film layer to experience abnormal pressure loss and fall off within a short period of time. At the same time, a large included angle can easily cause the friction component 2 to jam and move unsmoothly, which cannot truly reflect the film layer's strength.
[0068] By controlling the included angle within the range of 43° to 47°, the ratio of vertical pressure to horizontal friction can be optimized. This not only stably simulates the cumulative abrasive wear under wind and sand conditions, allowing the film layer to gradually detach in a realistic fatigue manner, but also ensures smooth movement and stable trajectory of the friction component 2, ensuring that the test process is uniform and controllable, and providing reliable support for the accurate quantification and high repeatability of the fastness value.
[0069] The angle between the friction element 2 and the surface film layer of the glass sample 1 to be tested can be 43°~45°, 45°~46°, 45°~47°, etc. For example, it can be 43°, 45°, or 47°.
[0070] In some embodiments, the friction element 2 is made of natural rubber or neoprene rubber.
[0071] Natural rubber and neoprene rubber have uniform texture and moderate friction, and possess good elasticity and wear resistance. During reciprocating friction, they are not prone to shedding, leaving residue, or damaging the glass substrate. They can stably simulate the abrasive fatigue wear experienced by the film layer under actual working conditions. At the same time, both materials are widely available and have good processing and molding properties, which can ensure strong consistency in friction performance and provide reliable material support for the accuracy and reproducibility of test results.
[0072] In some embodiments, the Shore A hardness of the friction element 2 is 65~75.
[0073] If the hardness of friction component 2 is less than 65, the material is too soft and easily deforms and wears severely. The wear intensity on the same trajectory continues to decrease, making it impossible to form a stable and consistent cumulative wear, which leads to a longer test cycle and makes it difficult to effectively distinguish the performance differences between different samples.
[0074] If the hardness is higher than 75, the friction component 2 will be too hard and cause excessive scratching and local stress concentration on the film layer. The film layer is prone to one-time scratch-type damage, which is inconsistent with the failure mechanism simulated in the test. At the same time, the excessively hard material will aggravate the abnormal damage to the film layer, resulting in lower results and unreliable data.
[0075] By controlling the hardness of friction component 2 within the range of 65~75, a friction interface with moderate hardness and stable wear resistance can be provided. This can achieve both gentle and uniform progressive cumulative wear and maintain long-term stable friction performance, making the test results accurate, highly discriminative, and highly reproducible, and suitable for standardized testing of photovoltaic glass film adhesion.
[0076] Optionally, the friction element 2 can be the rubber end of a rubber pen, with a cylindrical flat end and a diameter of 5.5 mm to 6.5 mm.
[0077] This makes it easy to fix the friction component 2 onto the test carriage 3, which is convenient and cost-effective.
[0078] In some embodiments, when rubbing the glass sample 1 to be tested with the friction member 2, the operator can manually fix it, or an automatic clamping assembly can be used to clamp and fix the glass sample 1 to be tested to prevent it from shifting during the rubbing process.
[0079] In some embodiments, between step S1, in which the friction member 2 rubs the same area of the surface film of the glass sample 1 to be tested for a preset number of times, and step S2, in which the friction area is observed to see if the film peels off, the glass film adhesion test method further includes cleaning the area of the surface film of the glass sample 1 to be tested that has been rubbed.
[0080] In this way, debris, film wear debris, and surface dust generated during the friction process can be removed in a timely manner, avoiding foreign matter residue covering or obscuring the true state of the film layer. This effectively prevents misjudgment or omission caused by debris interference, ensuring that the film layer can be clearly and accurately observed for true failure phenomena such as peeling and flaking. This improves the accuracy, reliability, and reproducibility of the test judgment, providing a stable and reliable observation basis for the accurate calculation of the film layer fastness value.
[0081] For example, to clean the area of the surface film layer of the glass sample 1 to be tested that has been rubbed, you can use oil-free and water-free compressed air or a bulb syringe to gently blow away surface debris, and then use lint-free paper, degreased cotton or microfiber cloth to gently wipe the rubbing track in one direction. If there are stubborn residues, you can dip a small amount of anhydrous ethanol or isopropanol to wipe quickly and blow dry immediately. Do not apply pressure or scratch the film layer throughout the process to ensure that there are no fibers, stains or solvent residues.
[0082] In some embodiments, before step S1, in which the same area of the surface film of the glass sample 1 to be tested is rubbed a predetermined number of times using the friction element 2, the glass sample 1 to be tested is cleaned and placed under standard environmental conditions for no less than 24 hours. The sample size is no less than 100 mm × 100 mm.
[0083] In some embodiments, step S2 of observing whether film peeling occurs in the friction area includes: observing whether film peeling occurs in the friction area using an optical microscope, wherein film peeling is determined to have occurred when the peeling or flaking area of the surface film is greater than 0.1 mm2, and film peeling is determined to have not occurred when the peeling or flaking area of the surface film is less than or equal to 0.1 mm2.
[0084] Using an optical microscope for observation can clearly identify minute defects such as film peeling and micro-peeling that are not visible to the naked eye, avoiding omissions and misjudgments caused by insufficient accuracy of visual observation, and accurately capturing film peeling phenomena.
[0085] The criteria for determining film peeling are limited to peeling or flaking areas greater than 0.1 mm². A unified and quantifiable threshold is established, eliminating the differences in subjective judgment among different operators and laboratories, and solving the problems of vague judgment standards and unreproducible results in traditional testing.
[0086] This standardizes the criteria for judging whether the film layer has failed, makes the strength values truly comparable, and effectively distinguishes glass products with different wear resistance levels.
[0087] In some embodiments, if no film peeling is observed in the friction area after the glass sample 1 under test has completed a preset number of rubbing cycles, the test is stopped and the strength value of the glass sample 1 under test is greater than the preset number of rubbing cycles.
[0088] If no film peeling is observed after the glass sample 1 has completed the preset number of rubbing cycles, it indicates that the film has high bonding strength and excellent wear resistance, which exceeds the wear requirements of conventional testing. Stopping the test at this time can save testing time, reduce equipment wear, and avoid invalid operations caused by excessive friction.
[0089] Recording the hardness value as the number of rubs greater than the preset number of rounds can clearly reflect the high performance level of the sample, maintain the standardization and uniformity of the test results, facilitate the performance comparison and grade classification between different samples, and is especially suitable for distinguishing the quality of ultra-high wear-resistant glass, providing a clear and intuitive basis for product selection and quality evaluation.
[0090] For example, taking a test cycle of 10 rubs as an example, the preset number of cycles can be 180 to 220. For instance, when the preset number of cycles is 200, the maximum test cycle is 20. If the film layer does not peel off after 20 test cycles, the test is terminated and recorded as greater than 200. This can save test time, reduce equipment wear and tear, and clearly demonstrate the high performance level of the sample.
[0091] In some embodiments, after the step of recording the strength value of the glass sample 1 to be tested, the glass film strength test method further includes: Take multiple identical glass samples and test their strength values respectively; The median of the fastness values of all the same type of glass sample 1 is taken as the fastness value of this type of glass sample.
[0092] By testing multiple identical glass samples, it is possible to effectively avoid the result deviations caused by surface defects, differences in film uniformity, or accidental factors in a single sample. Parallel tests can fully reflect the true average performance of the batch of glass and avoid errors in the overall evaluation caused by the distortion of a single data point.
[0093] Using the median as the final result can further reduce the impact of extreme outliers on the overall data. Even if individual samples show data that are too high or too low due to accidental factors, the median still represents a stable glass strength value, making the results more accurate and representative, and greatly improving the reliability of the test results.
[0094] Preferably, each group of the same type of glass sample 1 shall test no less than 3 samples.
[0095] Taking a test cycle of 10 rubs as an example, the durability values of conventional glass and wear-resistant glass were tested respectively. Figures 3 to 7 It can be seen that, Figure 3 These are the durability test results for conventional glass and abrasion-resistant glass disclosed in the embodiments of this application. Figure 4 This is a schematic diagram of conventional glass before the film layer peels off, as disclosed in the embodiments of this application. Figure 5 This is a schematic diagram of conventional glass after the film layer has peeled off, as disclosed in the embodiments of this application. Figure 6 This is a schematic diagram of the wear-resistant glass before the film layer peels off, as disclosed in the embodiments of this application. Figure 7This is a schematic diagram of the wear-resistant glass after the film layer has peeled off, as disclosed in the embodiments of this application. The fastness value of conventional glass tested by the test method of this application is 50, and the fastness value of wear-resistant glass is 70.
[0096] according to Figure 3 It can be seen that when both conventional glass and abrasion-resistant glass are tested for their strength using the test method of this application, for conventional glass, after selecting a friction area, no detachment is observed when the friction element rubs the friction area of the conventional glass 40 times; when the friction element rubs the friction area of the conventional glass 50 times, according to... Figure 4 It can be seen that some of the friction area has detached, but the detached area is less than 0.1 mm. It was determined that no film layer peeling occurred; when the friction component rubbed the friction area of the conventional glass 60 times, according to Figure 5 It can be seen that the area of detachment in the friction zone is greater than 0.1. The glass was determined to have a film peeling off, therefore the strength value of the conventional glass was 50.
[0097] For wear-resistant glass, a selected friction area was observed. After 40 rubs with the friction element, no detachment was observed in the friction area. This process was repeated, and after the 50th and 60th rubs, no detachment was observed in the friction area. However, after 70 rubs with the friction element, according to… Figure 6 It can be seen that there is slight flaking in the friction area, but the flaking area is less than 0.1 mm. It was determined that no film layer peeling occurred; when the friction component rubbed the friction area of the wear-resistant glass 80 times, according to Figure 7 It can be seen that the area of detachment in the friction zone is greater than 0.1. The glass was determined to have a film peeling off, therefore the strength value of the conventional glass was 70.
[0098] according to Figure 8 It can be seen that, Figure 8 This image shows a comparison of pencil hardness tests performed on conventional glass and abrasion-resistant glass, as disclosed in this application, and the tests conducted using the method described in this application. Using the existing pencil test method, the hardness test results for conventional glass and abrasion-resistant glass are identical; neither shows a permanent scratch when a pencil with a hardness of 9H is used to scratch the glass surface. Therefore, a pencil hardness of 9H (the highest grade) is the test result for both conventional glass and abrasion-resistant glass, and cannot distinguish between them. This demonstrates that the glass abrasion resistance test method disclosed in this application can clearly distinguish the abrasion resistance of two types of glass with similar hardness.
[0099] If the maximum and minimum values of the test strength results of multiple identical glass samples 1 exceed the set number of rounds, it indicates data abnormality and the test should be repeated. For example, the median of the test results of 3 samples is taken as the rubber strength of the glass sample. If the difference between the maximum and minimum values of the 3 sample strength results exceeds 50, the test should be repeated.
[0100] The above embodiments are only used to illustrate the technical solutions of this application and do not constitute a limitation. The embodiments can be freely combined without conflict. Although each embodiment has been described in detail, those skilled in the art should understand that modifications can be made to the technical solutions or equivalent substitutions can be made to the technical features, and such modifications or substitutions should all be covered within the scope of the technical solutions of this application.
Claims
1. A method for testing the adhesion of a glass film, characterized in that, include: A friction element is used to rub the same area of the surface film layer of the glass sample to be tested for a preset number of times, wherein the hardness of the friction element is less than the minimum hardness of the surface film layer. Observe whether the film layer peels off in the friction area, wherein the film layer peeling off is defined as visible peeling or flaking of the surface film layer; If no film peeling is observed in the friction area, repeat the above two steps until film peeling is observed in the friction area for the first time. One round of friction of the preset number of times is recorded as one test cycle. After removing the number of frictions in the test cycle in which the film peels off, the total number of frictions in the remaining test cycles is calculated, and the total number of frictions is recorded as the strength value of the glass sample to be tested.
2. The method for testing the adhesion of a glass film layer according to claim 1, characterized in that, The surface film layer has a starting point and a round trip point. The friction element moves from the starting point to the round trip point and then from the round trip point back to the starting point, which is recorded as one friction cycle.
3. The method for testing the adhesion of a glass film layer according to claim 2, characterized in that, The friction element moves in a linear reciprocating motion between the starting point and the reciprocating point, wherein the distance between the starting point and the reciprocating point is 45mm~55mm.
4. The method for testing the adhesion of a glass film layer according to claim 2, characterized in that, The process of rubbing the same area of the surface film of the glass sample under test with a friction element for a preset number of cycles includes: A test trolley capable of reciprocating along the horizontal direction is used to drive the friction component to rub the same area of the surface film of the glass sample under test for a preset number of times. The test trolley has a counterweight that can apply a preset downward vertical pressure to the friction component.
5. The method for testing the adhesion of a glass film layer according to claim 2, characterized in that, The friction element moves at a speed of 8 mm / s to 12 mm / s between the starting point and the return point.
6. The method for testing the adhesion of a glass film layer according to claim 2, characterized in that, The friction element is a rod-shaped structure, and the angle between the friction element and the surface film layer of the glass sample to be tested is 43°~47°; and / or, The friction element is made of natural rubber or neoprene rubber, and its Shore A hardness is 65~75.
7. The method for testing the adhesion of a glass film layer according to claim 1, characterized in that, Between the steps of rubbing the same area of the surface film of the glass sample to be tested with a friction element for a preset number of times and observing whether the film peels off in the rubbed area, the glass film adhesion test method further includes: Clean the area of the surface film layer of the glass sample to be tested that has been rubbed.
8. The method for testing the adhesion of a glass film layer according to claim 1, characterized in that, The steps for observing whether the film layer has peeled off in the friction area include: The friction area was observed using an optical microscope to determine if film peeling or flaking occurred. Specifically, if the area of peeling or flaking of the surface film was greater than 0.1 mm, it was considered a positive result. The occurrence of film peeling is determined when the peeling or flaking area of the surface film is less than or equal to 0.1 mm. It is determined that no film layer has peeled off.
9. The method for testing the adhesion of a glass film layer according to claim 1, characterized in that, If no film peeling is observed in the friction area after the glass sample under test has completed a preset number of rubbing cycles, the test is stopped, and the strength value of the glass sample under test is greater than the preset number of rubbing cycles.
10. The method for testing the adhesion of a glass film layer according to claim 1, characterized in that, After recording the strength value of the glass sample to be tested, the glass film strength test method further includes: Take multiple identical glass samples to be tested and test their fastness values respectively; The median of the fastness values of all the same type of glass samples to be tested is taken as the fastness value of this type of glass sample.
